Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3102/0013189x19860814
|View full text |Cite
|
Sign up to set email alerts
|

Worsening School Segregation for Latino Children?

Abstract: A half century of research details how segregating racial groups in separate schools corresponds with disparities in funding and quality teachers and culturally narrow curricula. But we know little about whether young Latino children have entered less or more segregated elementary schools over the past generation. This article details the growing share of Latino children from low-income families populating schools, 1998 to 2010. Latinos became more segregated within districts enrolling at least 10% Latino pupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…Hispanics' concentration in less selective institutions results in part from their comparatively limited academic preparation, which stems from historical educational segregation in less well-resourced primary and secondary schools (e.g. Gandara and Contreras 2010;Fuller et al 2019). This condition also results from Hispanics' preferences in choosing tertiary institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hispanics' concentration in less selective institutions results in part from their comparatively limited academic preparation, which stems from historical educational segregation in less well-resourced primary and secondary schools (e.g. Gandara and Contreras 2010;Fuller et al 2019). This condition also results from Hispanics' preferences in choosing tertiary institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Latinx school segregation is rising nationally across all grade levels. Orfield and others (2014) found that exposure-a measure that reflects contact or interaction among student groups-to white students decreased nationally between 1968 and 2011, especially in the West and Midwest (see also Fuller et al 2019). Economic segregation-which is often concurrent with racial segregation-is also increasing.…”
Section: School Racial and Economic Segregationmentioning
confidence: 99%
“…De esta forma, los primeros pasos en la investigación sobre segregación escolar giraron en torno a la segregación racial, antes centrada en la segregación de afrodescendientes y, actualmente, en la segregación de otras minorías, como las personas procedentes de Latinoamérica (p. ej. Fiel y Zhang, 2018;Fuller et al, 2019;Santiago, 2019).…”
Section: Revisión De La Literaturaunclassified